2013
DOI: 10.5539/jel.v2n1p211
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics and English, Two Languages: Teachers’ Views

Abstract: English is an international language used all over the world. Mathematics is the language of sciences but it is also a language used in everyday life. Although both are perceived as languages, mathematics and English are considered as two completely distinct disciplines. In this paper we first discuss English and mathematics as languages. Then we present interviews conducted with five mathematics and English teachers in order to explore their views regarding issues of language features, ways of teaching and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…In Mathematics, we use numbers and symbols, to construct "words" and "sentences" in mathematical constructions or what is called "mathematical story" as in solutions of exercises, problems. Thus, Mathematics, like languages, has also its own grammar or as (Leshem & Markovits: 2013) called it the mathematical logic as a criterion of validity or falsity of statements.…”
Section: Mathematics and English Language Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mathematics, we use numbers and symbols, to construct "words" and "sentences" in mathematical constructions or what is called "mathematical story" as in solutions of exercises, problems. Thus, Mathematics, like languages, has also its own grammar or as (Leshem & Markovits: 2013) called it the mathematical logic as a criterion of validity or falsity of statements.…”
Section: Mathematics and English Language Relationshipmentioning
confidence: 99%
“…But in order to present all these types of languages, teachers have to master the foreign language as well as the mathematical language. Leshem & Markovits (2013) indicated that Most mathematics teachers in general education classrooms are monolingual and don't have expertise in second language instruction. One of the best ways to deal with this dilemma is to collaborate with a bilingual or English-as-a-second-language (ESL) specialist.…”
Section: Chapman (1993) and Jaber (2004) Identified Types Of Language...mentioning
confidence: 99%
“…Sie argumentieren, dass Englisch die internationale Sprache der Welt ist, während die Mathematik sowohl die Sprache der Wissenschaft als auch die Sprache des täglichen Lebens ist. Sie vergleichen Mathematik und Englisch und versuchen nachzuweisen, dass beide ein ähnliches Denken des Einzelnen erfordern (Leshem S., 2013). Die enge Beziehung und die Ähnlichkeiten im Denken zwischen diesen beiden Wissenschaften werden auch in einer Studie von Li und Wang aus dem Jahr 2013 untersucht (Li F., 2013).…”
Section: Die Verbindung Der Mathematik Und Der Sprachwissenschaftunclassified
“…Mathematics uses internationally recognised numbers, mathematical symbols, and grammar as Leshem and Markivits (2013) have noted. These are linked to the LoLT, regardless of what that language might be.…”
Section: Language As Central To Learner Ability In the Assessment Of Mathematicsmentioning
confidence: 99%